La planificación estratégica como instrumento de gestión institucional en la unidad educativa “ramón barba naranjo” del cantón Latacunga, provincia de Cotopaxi para el período 2016-2020. - Yánez Ávila, María Eugenia (2017)
The Strategic Planning is a tool very importance for the United Educative “Ramón Barba Naranjo”, for the achievement of its objectives and institutional goals that go likewise according with its vision and mission that he/she has, achieving the invigoration of its management and educational organization, identifying the internal and external aspects that it benefits them and it affects them to be able to develop its management in the educational environment you could evidence through the analysis of FODA, it is so it was possible to structure the Tactical Operative Plan, which contains the qualification project to the educational ones that at the present time is important for the teaching-learning that you/they require the demands of the environment. You the importance that has the elaboration of a Strategic Planning for the institution that makes reference confirms therefore from how he/she has come being unwrapped from its creation until the present time, but also of how to be projected toward the future and power take the due decisions that are necessary in an opportune and certain moment according to the requirements that presents the institution. In the design of Strategic Plantation he/she was derived a pertinent methodology to the characteristics of the organization; conserving the general logic of the prospective product of a process of strategic definition that improves the social and collective commitment substantially of offering an academic formation of quality.